2018
DOI: 10.1111/jocn.14165
|View full text |Cite
|
Sign up to set email alerts
|

Stress and ways of coping among nurse managers: An integrative review

Abstract: Hospital and nurse administrators play an important role in promoting supportive structures for daily professional practice for nurse managers through staffing, organisational resources, support services, leadership and stress management training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
138
2
8

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(152 citation statements)
references
References 53 publications
4
138
2
8
Order By: Relevance
“…Although NMs in this study mentioned strategies to support nurse well‐being, many felt powerless and unable to make changes. Similar to the findings in this current study, other studies have described how NMs see themselves in an inferior position, lacking the influence, autonomy and confidence to participate in strategic planning (Labrague, McEnroe‐Petitte, Leocadio, Van Bogaert, & Cummings, ; Ogle & Glass, ; Paliadelis, ). Lack of autonomy may be linked to NMs poor academic qualifications, upper management's unclear understanding of the NM role or a lack of trust in NMs ability to make decisions (Brown, Fraser, Wong, Muise, & Cummings, ; Hewko, Brown, Fraser, Wong, & Cummings, ; Roche, Duffield, Dimitrelis, & Frew, ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Although NMs in this study mentioned strategies to support nurse well‐being, many felt powerless and unable to make changes. Similar to the findings in this current study, other studies have described how NMs see themselves in an inferior position, lacking the influence, autonomy and confidence to participate in strategic planning (Labrague, McEnroe‐Petitte, Leocadio, Van Bogaert, & Cummings, ; Ogle & Glass, ; Paliadelis, ). Lack of autonomy may be linked to NMs poor academic qualifications, upper management's unclear understanding of the NM role or a lack of trust in NMs ability to make decisions (Brown, Fraser, Wong, Muise, & Cummings, ; Hewko, Brown, Fraser, Wong, & Cummings, ; Roche, Duffield, Dimitrelis, & Frew, ).…”
Section: Discussionsupporting
confidence: 89%
“…This study provides evidence suggesting that collaboration and communication between NMs and upper management must be improved. A literature review by Labrague et al () suggests that NM's coping abilities may be enhanced if organisations ensure NM social support and promote NM job control. Other studies suggest that NMs who participate in organisational decision‐making experience higher levels of well‐being and are more likely to contribute to healthy workplaces (Adriaenssens, Hamelink, & Van Bogaert, ; Djukic, Jun, Kovner, Brewer, & Fletcher, ; Kath, Stichler, & Ehrhart, ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hewko et al (2015), ongoing mentorship is another key component of a workplace setting that promotes nurse managers' retention and likely improves job satisfaction. Findings from Labrague et al (2018) across diverse workplace settings. Given these findings, Hewko et al (2015) suggest that to promote a trusting and empowering workplace environment organisations should focus on hiring upper management personnel who exhibit resonant leadership, are supportive of nurse managers and show nurse managers that they are valued employees.…”
Section: Leadershipmentioning
confidence: 99%
“…In most health systems, nursing wards and departments are run by an experience registered nurse (RN) appointed to a management position, combining the clinical leadership of nurses with the managerial responsibilities of operations. These nurse managers play a crucial role in the organisation and delivery of health services: creating environments where nurses can provide quality patient care, while ensuring that organisational imperatives are met (Labrague, McEnroe‐Petitte, Leocadio, Bogaert, & Cummings, ; Pegram, Grainger, Sigsworth, & While, ). A growing body of research has demonstrated the stressors and tensions inherent in performing these clinical‐managerial hybrid roles (Burgess & Currie, ; Hewko, Brown, Fraser, Wong, & Cummings, ; Labrague et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These nurse managers play a crucial role in the organisation and delivery of health services: creating environments where nurses can provide quality patient care, while ensuring that organisational imperatives are met (Labrague, McEnroe‐Petitte, Leocadio, Bogaert, & Cummings, ; Pegram, Grainger, Sigsworth, & While, ). A growing body of research has demonstrated the stressors and tensions inherent in performing these clinical‐managerial hybrid roles (Burgess & Currie, ; Hewko, Brown, Fraser, Wong, & Cummings, ; Labrague et al, ). However, there is much less research on nurse managers' level of engagement in the diverse activities that comprise their roles (Bjerregård Madsen, Kaila, Vehviläinen‐Julkunen, & Miettinen, ), in particular the balance between clinical and other responsibilities.…”
Section: Introductionmentioning
confidence: 99%